Induced polyploidy in inter‐subspecific maize hybrids to reduce heterosis breakdown and restore reproductive fertility. (11th September 2014) - Niazi, I. A. K.; Rauf, S.; Teixeira da Silva, J. A.; Iqbal, Z.; Munir, H.
Abstract The aim of this study was to reduce the breakdown of hybrid vigour by crossing maize × teosinte subspecies through induced tetraploidy and to improve the biomass and reproductive fertility of the induced tetraploids. To achieve this, seeds of maize breeding lines selected from an open‐pollinated population 'Sargodha‐2002' and a maize × teosinte cross were germinated in colchicine solution (0·25, 0·5 or 1·0%) until they had a thick radical and protruded plumule. Colchicine at 0·5% induced the highest number of tetraploids with the lowest number of chimeric plants. The induced tetraploids of maize and maize × teosinte crosses showed a significant (P ≤ 0·05) increase in leaf area (5 and 14%), total soluble solids (20 and 18%), leaf oil percentage (42 and 12%) and leaf crude protein contents (10 and 14%) in leaves relative to the diploid subspecies. Moreover, induced tetraploidy also arrested hybrid vigour by slowing down the decay of heterosis in progenies (4x) for plant height, leaf biomass and leaf oil percentage. Induced maize × teosinte hybrid tetraploids selected for frequent bivalent chromosome pairing resulted in higher seed setting cob−1 (increased 58%), pollen fertility (increased 59%) and seed setting percentage (increased 100%) than the quadrivalent variant.